The Correlation between Internet Literacy and Passive Vocabulary Size - Riza Weganofa; Rizky Lutviana (Bina Nusantara University, 2018)
This research aimed at describing the correlation between students’ internet literacy and their passive vocabulary size. The findings of this research were expected to predict how much the two variables correlate. This research was beneficial as inter internet users in Indonesia were growing in numbers (55 billion users in 2011), and most of them were students. Their intensity in using internet would affect on education, later. Thus, it was important to see whether there was a strong positive correlation between students’ internet literacy and their passive vocabulary size. Passive vocabulary became the limitation of this research as it could explain how big students’ ‘vocabulary reservoir,’ and thus, it could predict the active vocabulary size.This was a correlational research involving randomly 81 senior students of English Education Department. The instruments used were a set of vocabulary test, and a questionnaire on internet literacy. Using two-tailed significant level, it is found that the result of rho is -0,001 with 0,993 of significant level. Therefore, there is no correlation between students’ internet literacy and their passive vocabulary size. It can be concluded that there are other factors which affect students’ passive vocabulary.